Neurodevelopmental outcomes in children in relation to placental abruption. (22nd April 2016) - Ananth, CV; Friedman, AM; Lavery, JA; VanderWeele, TJ; Keim, S; Williams, MA
Abstract : Objective: Placental abruption has a profound impact on perinatal mortality, but implications for neurodevelopment during childhood remain unknown. We examined the association between abruption and neurodevelopment at 8 months and 4 and 7 years and evaluated the extent to which these associations were mediated through preterm delivery. Design: Secondary analysis of a multicenter prospective cohort study. Setting: Multicenter US National Collaborative Perinatal Project (1959–76). Population: Women that delivered singleton live births. Methods: Analyses of IQ scores were based on marginal structural models (MSM) to account for losses to follow‐up. We also carried out a causal mediation analysis to evaluate if the association between abruption and cognitive deficits was mediated through preterm delivery, and performed a sensitivity analysis for unobserved confounding. Main outcome measures: We evaluated cognitive development based on the Bayley scale at 8 months (Mental and Motor Scores), and intelligent quotient (IQ) based on the Stanford–Binet scale at 4 years and the Wechsler Intelligence Scale for Children at 7 years. Results: The confounder and selection‐bias adjusted risk ratio (RR) of abnormal 8‐month Motor and Mental assessments were 2.35 (95%CI 1.39, 3.98) and 2.03 (95%CI 1.13, 3.64), respectively, in relation to abruption. The associations at 4 years were attenuated and resolved at 7 years. The proportion of children with abruption‐associated neurological deficits mediated through preterm delivery ranged from 27 to 75%. Following adjustment for unobserved confounding the proportion mediated through preterm delivery was attenuated. Conclusion: The effect of abruption on neurodevelopmental outcomes appears restricted to an effect that is largely mediated through preterm delivery. Tweetable abstract: Increased risk of cognitive deficits in relation to abruption appears to be mediated through preterm delivery. Tweetable abstract: Increased risk of cognitive deficits in relation to abruption appears to be mediated through preterm delivery.